Miftahul Muta'allimin Islamic Boarding School: From the Classik Book (Kitab Kuning) to Scientific Traditions - Abdul Hanan (International Journal of Nusantara Islam, 2022)
This study analyzes the Javanese pegon method in Islamic boarding schools in Indonesia, especially at the Miftahul Muta'allimin Islamic Boarding School in Cirebon. Currently, during the digital media era, this phenomenon appears a lot, namely how the Javanese Pegon method answers its existence. Researchers will test the explanation about the presence of the Javanese Pegon meaning method as it has become a tradition of learning in Islamic boarding schools in general, we need to limit the discussion in this paper. How does the Javanese Pegon meaning become one of the methods for understanding the Classik Book   (Kitab Kuning), What are the advantages of the Javanese Pegon meaning method in the process of understanding the Classik Book   (Kitab Kuning), What are the inhibiting factors in applying the Pegon Javanese meaning method to understanding the Classik Book   (Kitab Kuning). The approach that will be used is of course phenomenology and with an observation framework.